Associations between motor cortex inhibition & gait variability - Swanson, Clayton W., author; Fling, Brett W., author (Colorado State University. Libraries, 2017)
Motor cortex inhibition is significantly associated with complex bimanual control of the upper extremities. It remains unclear whether this same relationship exists for the lower extremities. We utilized transcranial magnetic stimulation to assess motor cortex inhibition and wireless, inertial sensors to quantify gait variables to assess how cortical inhibition contributes to the control of gait in healthy, young adults. Gait cycle duration variability was significantly correlated to right motor cortex inhibition. The results of this study indicate that motor cortex inhibition may be associated with complex components of gait in a similar fashion to its association with bimanual control.
284 - Clayton W. Swanson
Keywords: TMS; gait variability; transcranial magnetic stimulation